Assessing the Impact of the Philippine Sin Tax Reform Law on the Demand for Cigarettes - Austria, Myrna S. (Animo Repository, 2018)
One of the significant legislations during the Aquino Administration was Republic Act 10351, otherwise known as the Sin Tax Reform Act of 2012. Considered a landmark legislation, the law addressed the long-standing structural weaknesses of the country’s tobacco tax system. It considerably increased the specific excise tax on tobacco and tobacco products, simplified the tax structure, removed the price classification freeze and indexed the tax rates to address inflation. Prior to the reform, tobacco taxation in the country followed a complex four-tiered tax system using a tax base freeze at 1996 price levels. And since the excise tax was not indexed to inflation, prices of tobacco products in the country were among the cheapest in the world despite the increases in excise tax over the years (Quimbo et al., 2012). In contrast, the current law provides a two-tiered system effective January 2013 with a gradual shift to a single and uniform rate taxation starting 2017, after which the rate will be increased by 4% every year effective January 2018. The current system is considered simpler and more efficient in raising tobacco taxes.